Secularism and the Issue of Islam in the Aceh Conflict: A Framing Process Approach - Ansori, Mohammad Hasan (Center for Research and Development of Religious Literature and Heritage, 2012)
Aceh conflict is widely recognized as one of the most protracted and violent conflicts not only in Southeast Asia, but also in the globe. This study intends to look at the secessionist conflict from he social movement perspective, and specifically from the theoretical instrument of framing process. This study goes a little further by getting engaged with the strategic issue of Islam in the region. In lieu of commonly adopted macro and structural analysis of the conflict, this study methodologically instead applies micro and dynamic analysis of the conflict. In general, this study primarily argues that the framing strategy adopted by Free Aceh Movement (GAM) is clearly secular in nature, and/or far away from the Islam-nuanced religiosity and spirit. However; Islam is often exploited particularly for mass mobilization. The movement